Factors associated with injuries related to chainsaw tree felling in Japan. Issue 3 (2nd September 2019) - Tobita, Kyoko; Nitami, Toshio; Yoshioka, Takuyuki
ABSTRACT: To examine the causes of chainsaw-related injuries and fatalities in tree felling work in Japan, we determined trends in fatal accidents occurring during chainsaw tree felling, as well as factors influencing injuries related to this work. We further explored the extent to which such accidents might be prevented by education. Our analysis was based on 2000–2014 data released by various Japanese government organizations. At the prefecture scale, there was a strong correlation between timber production volume and the number of fatal accidents during chainsaw felling. Accidents occurred most frequently on Fridays, and fatal accidents occurred most frequently around 9:00 a.m. and 3:00 p.m. Among the 14 factors associated with tree felling accidents, correct setting of the notch and hinge might have prevented 33.6% of all factors. We conclude that increased education to improve notch and hinge setting would be effective in chainsaw felling accident prevention.